2015
DOI: 10.1016/j.ijmyco.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A rare localization of tuberculosis of the wrist: The scapholunate joint

Abstract: The tuberculosis of the hand and the wrist is a rare entity. Affecting the scapholunate joint is exceptional. It is usually diagnosed at an advanced stage of carpal destruction, due to slowly development of the symptoms. We report the case of a 58-year-old female, presenting as wrist pain for 3 months. Clinical study showed a local swelling in the left wrist, the mobility of the wrist was normal but painful at the end of motion. The diagnosis of osteoarticular tuberculosis was suspected after radiological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Sbai et al reported a case of scapholunate joint TB with tenosynovitis of the extensor tendons of the wrist 14. However the lytic osseous lesion in their patient was in the scaphoid, that spread to the scapholunate joint contiguously.…”
Section: Discussionmentioning
confidence: 96%
“…Sbai et al reported a case of scapholunate joint TB with tenosynovitis of the extensor tendons of the wrist 14. However the lytic osseous lesion in their patient was in the scaphoid, that spread to the scapholunate joint contiguously.…”
Section: Discussionmentioning
confidence: 96%
“…When pathologies develop to the edge of the articular surface, the articular cartilage erodes and the subchondral bone is destroyed. With the destruction of the carpal bones, the spaces are lled by necrotic tissue resulting in arthritis and deformity of the affected carpal joint [12]. Chandrasekharan et al believe that tuberculosis of the wrist joint can be histologically divided into three stages.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Prakash [4] reported isolated involvement of the capitate. In 2015, Sbai et al [5] and Goel et al [6] reported isolated scapholunate and hamate involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Common sites of primary osseous focus are the os capitatum or distal end of the radius [2]. Very few cases have been reported of isolated involvement of a single bone or joint in the wrist or hand [3][4][5][6][7][8]. Isolated involvement of the hamate, in particular, is even rarer.…”
Section: Introductionmentioning
confidence: 99%